Analisis Kasus Cyber Crime Di Indonesia Dan Tantangan Penegakan Hukum Dalam Menghadapinya - Azzahra, Melani; Nurwati; Teguh Rama Prasja; M Rendi Aridhayandi (Jurnal Surya Kencana Satu : Dinamika Masalah Hukum dan Keadilan, 2025)
The development of information technology and the internet has had a significant impact on various aspects of life, with many positive and negative effects that cannot be ignored. One of the negative impacts is the increasing ease with which criminals can commit cyber crimes through the virtual world. Information technology crimes generally refer to criminal activities involving computers or computer networks, but also encompass traditional criminal activities that use computers or computer networks as tools to facilitate or enhance the efficiency of the crime. The purpose of this research is to examine various cases of cyber crime that occur in Indonesia. In addition, it discusses the main challenges in law enforcement related to cyber crime in Indonesia. This research method uses a descriptive analysis methodology. Data were collected through literature studies, including books, scientific articles, research reports, and news related to cybercrime in Indonesia. The research results show that the development of digital technology has opened up opportunities for various forms of cybercrime, and there are challenges faced in enforcing cybercrime laws in Indonesia.